2016
DOI: 10.1073/pnas.1520387113
|View full text |Cite
|
Sign up to set email alerts
|

Lmx1a and Lmx1b regulate mitochondrial functions and survival of adult midbrain dopaminergic neurons

Abstract: The LIM-homeodomain transcription factors Lmx1a and Lmx1b play critical roles during the development of midbrain dopaminergic progenitors, but their functions in the adult brain remain poorly understood. We show here that sustained expression of Lmx1a and Lmx1b is required for the survival of adult midbrain dopaminergic neurons. Strikingly, inactivation of Lmx1a and Lmx1b recreates cellular features observed in Parkinson's disease. We found that Lmx1a/b control the expression of key genes involved in mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 54 publications
5
102
0
Order By: Relevance
“…The ectopic presence of TH + cells in the striatum of the Dat Cre Fbxo7 −/fl mice, though remarkable, is not unique to this study . TH + cells occur naturally in the striatum , increasing in number following loss of nigrostriatal input in surgically lesioned animals and in transgenic mice with mutations in DA‐associated genes . They have also been observed in healthy and Parkinsonian post‐mortem human brains .…”
Section: Discussionmentioning
confidence: 73%
“…The ectopic presence of TH + cells in the striatum of the Dat Cre Fbxo7 −/fl mice, though remarkable, is not unique to this study . TH + cells occur naturally in the striatum , increasing in number following loss of nigrostriatal input in surgically lesioned animals and in transgenic mice with mutations in DA‐associated genes . They have also been observed in healthy and Parkinsonian post‐mortem human brains .…”
Section: Discussionmentioning
confidence: 73%
“…LIM domain containing proteins have diverse biological functions, often shuttling between the nucleus and the cytoplasm, potentially even in a redox‐regulated manner, acting as adaptors or scaffolds to support the assembly of multimeric protein complexes, and can also contribute to the regulation of localization . Specifically, LMX1B controls the expression of key genes involved in mitochondrial functions . The FHL1 gene is predominantly expressed in skeletal and cardiac muscle, and its mutations are causative for several types of hereditary myopathies.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term and tissue tissue-specific autophagy responses are controlled at the transcriptional level by diverse families of transcription factors (Fullgrabe, Ghislat et al, 2016, Fullgrabe, Klionsky et al, 2014, but the transcriptional pathways that regulate autophagy gene expression in human mDANs remain elusive. Significantly, in the conditional Lmx1a/Lmx1b knockout mice, post-mitotic mDAN functional decline was associated with dysregulated autophagy, reduced mitochondrial function, and elevated mitochondrial oxidative stress (Doucet-Beaupre et al, 2016, Laguna et al, 2015. This suggests that LMX1A/LMX1B contribute to the expression of autophagy and mitochondrial quality control genes in mDANs.…”
Section: Introductionmentioning
confidence: 98%
“…-synuclein-positive and distended axonal terminals) and behavioural abnormalities consistent with PD (Doucet-Beaupre, Gilbert et al, 2016, Laguna, Schintu et al, 2015. With this in mind, it is noteworthy that Lmx1a expression declines with age in the mouse brain (Doucet-Beaupre et al, 2016, Laguna et al, 2015, while LMX1B levels have been reported to inversely correlate with disease progression in the brains of PD patients (Laguna et al, 2015, Xia, Zhang et al, 2016. In addition, LMX1A/LMX1B polymorphisms have been linked (albeit weakly) to PD ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation